Religion-based perspective and influences on use of animals in research - Karunarathna, Ureshani; Yapa, Piumika; Menike, A. I. S.; Ganesh, Lakshy; Ganesh, KSV Angu Bala; Thilakarathna, Amandi; Gunatilake, Mangala; Singh, Vijay Pal; Md Isa, Muhammad Lokman; Poosala, Suresh; Baumans, Vera (Laboratory Animal Scientists' Association (LASA) India, 2024)
All religions are concerned with the care and welfare of animals, paying respect to the animals. Beliefs and attitudes towards animals that are based on religious and cultural perspectives play an important role in human-animal relationships. Christian attitudes have been impacted by Western philosophical consideration of human-animal relationships, whereas Eastern religions (Hinduism, Buddhism, and Islam) and their teachings impose varying values on the existence of animals. Even though their justifications affect the views of individuals and their feelings toward animal testing, scientists continue to employ animals in their research. Even though it is impossible to underestimate the worth of a life, this article describes the religious perspectives on animal existence and harming to animals.